2008
DOI: 10.1071/pc080279
|View full text |Cite
|
Sign up to set email alerts
|

Towards restoration of Hawaiian tropical dry forests: the Kaupulehu outplanting programme

Abstract: Hawaiian tropical dry forests contain diverse assemblages of woody canopy species, including many endemic and endangered species that warrant conservation attention before completely disappearing. Today, tropical dry forests in Hawaii are not viable ecosystems. Poor land use practices, fragmentation, non-native plant invasions, and inadequate native vegetation regeneration are all factors that have contributed to their endangerment. Only an ambitious restoration programme that includes non-native ungulate excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Over 40% of all at-risk plant species occur in dry or rocky habitats where low water availability is a barrier to recovery (Kew Royal Botanic Gardens 2010), including the highly endangered dry-lands where we work in Hawaii (Dobson et al 1997). Reintroduction programs have had limited success in many drylands due to a low probability of establishment and high levels of plant mortality (e.g., Cordell et al 2008). Often planting areas are arbitrarily or opportunistically selected without consideration of microclimatic gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Over 40% of all at-risk plant species occur in dry or rocky habitats where low water availability is a barrier to recovery (Kew Royal Botanic Gardens 2010), including the highly endangered dry-lands where we work in Hawaii (Dobson et al 1997). Reintroduction programs have had limited success in many drylands due to a low probability of establishment and high levels of plant mortality (e.g., Cordell et al 2008). Often planting areas are arbitrarily or opportunistically selected without consideration of microclimatic gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient loading [i.e., applying fertilizers past the point of increased growth to where the seedlings take up excess nutrients (luxury consumption)] has also been shown to increase N concentration in Acacia koa seedlings (Dumroese et al 2009), which should help them to establish well in N-poor grasslands. Cordell et al (2008) found that vines had twice the survival rate of tree seedlings in an extremely dry site and recommended these for initial planting on disturbed sites. Coordination with field crews regarding timing of planting is critical, as trees can be vulnerable to frost at high elevation sites during winter months (Scowcroft and Jeffrey 1999), and managers need to be able to plant dry sites during the wettest part of the year.…”
Section: Production Of Improved Planting Materialsmentioning
confidence: 98%
“…Another Hawaiian dry forest study observed an outplanting tree seedling survival rate of 34%, but that effort was more labor intensive, since the seedlings received supplemental watering for six months (Cordell et al 2008). Comparing costs and results of planting seedlings verses broadcast seeding in this environment may be a needed direction for future research.…”
Section: Figure 2 Mean Seedling (± Se) Counts By Treatment Combinatimentioning
confidence: 99%